2023
DOI: 10.3390/molecules28041725
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Inhibits the Stemness of Gastric Cancer Cells by Regulating the GRP78-TGF-β1 Signaling Pathway and Macrophage Polarization

Abstract: Cancer stemness is the process by which cancer cells acquire chemoresistance and self-renewal in the tumor microenvironment. Glucose-regulated protein 78 (GRP78) is a biomarker for gastric cancer and is involved in cancer stemness. By inducing cancer stemness in various types of cancer, the polarization of macrophages into tumor-associated macrophages (TAMs) controls tumor progression. Betulinic acid (BA) is a bioactive natural compound with anticancer properties. However, whether GRP78 regulates TAM-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Accumulative research has reported that EVs containing microRNAs, circular RNAs, long non‐coding RNAs (lncRNAs) or proteins derived from GC cells regulated the polarisation of TAMs after the internalisation by macrophages 52,64–71 . Notably, natural compounds extracted from plants, such as flavokawain B, sophoridine, diosmetin, elian granules and betulinic acid, were found to enhance the polarisation of M1 TAMs 72–76 . Additionally, pentraxin‐3 was found to inhibit the polarisation of M2 TAMs by reducing cells secreting IL‐4 and IL‐10 via the inhibition of the phosphorylation of JNK1/2 in GC cells 77 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulative research has reported that EVs containing microRNAs, circular RNAs, long non‐coding RNAs (lncRNAs) or proteins derived from GC cells regulated the polarisation of TAMs after the internalisation by macrophages 52,64–71 . Notably, natural compounds extracted from plants, such as flavokawain B, sophoridine, diosmetin, elian granules and betulinic acid, were found to enhance the polarisation of M1 TAMs 72–76 . Additionally, pentraxin‐3 was found to inhibit the polarisation of M2 TAMs by reducing cells secreting IL‐4 and IL‐10 via the inhibition of the phosphorylation of JNK1/2 in GC cells 77 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%
“…52,[64][65][66][67][68][69][70][71] Notably, natural compounds extracted from plants, such as flavokawain B, sophoridine, diosmetin, elian granules and betulinic acid, were found to enhance the polarisation of M1 TAMs. [72][73][74][75][76] Additionally, pentraxin-3 was found to inhibit the polarisation of M2 TAMs by reducing cells secreting IL-4 and IL-10 via the inhibition of the phosphorylation of JNK1/2 in GC cells. 77 IL-4, a cytokine, was widely reported to elicit M2 polarisation, while Zhao and Liu demonstrated that the IL-4-stimulated heparin binding-epidermal growth factor (HB-EGF)-dependent transactivation of EGFR inhibited the polarisation of M2 TAMs induced by IL-4-stimulated STAT6 activation.…”
Section: Regulation Of the Phenotypic Polarisation Of Tams In Gcmentioning
confidence: 99%
“…Cell surface GRP78-targeted CAR-T cells have also been shown to be effective in treating human pancreatic cancer [ 14 ]. In addition, HSPA5 has been shown to affect the stemness profile of cancer cells in esophageal, glioblastoma, gastric and breast cancers [ [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%